Toll-like receptor-dependent antiviral responses at the maternal–fetal interface - Xiao-Rui Liu; Xiao-Wei Wei; Yi Lin (Reproductive and Developmental Medicine, 2020)
The maternal–fetal interface is a key barrier to protect the fetus from infection. Toll-like receptors (TLRs) at the maternal–fetal interface are involved in antiviral responses. TLRs are expressed in both maternal decidua and fetal trophoblasts. Virus-induced activation of TLR signaling pathways triggers the release of interferon-related antiviral molecules and other inflammatory cytokines and/or chemokines by the host innate immune system, which may disrupt immune tolerance at the maternal–fetal interface and lead to pregnancy complications. In this review, we summarize the state of knowledge on the most common viral infections during pregnancy, antiviral TLR responses at the maternal–fetal interface, and TLR-associated pregnancy complications.